Comparison of Efficacy and Safety of Single and Double Immune Checkpoint Inhibitor-Based First-Line Treatments for Advanced Driver-Gene Wild-Type Non-Small Cell Lung Cancer: A Systematic Review and Network Meta-Analysis - Xu, Qian; Zhang, Xue; Huang, Miao; Dai, Xin; Gao, Jing; Li, Song; Sheng, Lei; Huang, Kai; Wang, Jian; Liu, Lian (Frontiers in Immunology, 2021)
Background Immune checkpoint inhibitors (ICIs) have improved survival for advanced wild-type non-small cell lung cancer (NSCLC) significantly, but few studies compared single ICI (SICI)-based treatments and double ICIs (DICI)-based treatments. We summarized the general efficacy of ICI-related treatments, compared the efficacy and safety of SICI-based [programmed death 1 (PD-1)/programmed death-ligand 1 (PD-L1) or cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) inhibitors ± chemotherapy (CT)] and DICI-based (PD-1/PD-L1 inhibitors+CTLA-4 inhibitors ± chemotherapy) treatments vs. CT in the first-line treatment. Methods We included phase II/III randomized controlled trials (RCTs), including patients with histologically confirmed stage IIIB–IV driver-gene wild-type NSCLC who received first-line ICI-related therapy in at least one arm. PubMed, Embase, and Cochrane Library were searched from January 1, 2005, to December 31, 2020. This network meta-analysis was performed in a Bayesian framework using GEMTC and JAGS package in R.3.6.1. The research was registered with PROSPERO (CRD42020184534). Results Twenty RCTs were involved, including 13,032 patients and 17 treatment regimens. The results showed that ICI-based therapies could provide a pooled median overall survival (mOS) (POS) of 15.79 (95% CI: 14.85–16.73) months, and there were no significant differences in OS, progression-free survival (PFS), objective response rate (ORR), and grade 3 or higher adverse events (≥3AEs) between DICI-based treatments (POS: 14.81, 12.11–17.52 months) and SICI-based treatments (POS: 16.17, 14.59–17.74 months) in overall patients. However, DICI-based treatments had significantly prolonged the OS over SICI-based treatments in squamous and PD-L1 <1% subgroups. The ranking of OS benefit by Bayesian surface under the cumulative ranking curve (SUCRA) spectrum showed that DICI+chemotherapy ranked first for overall population and subgroups including squamous, non-squamous, any level of PD-L1 expression, smoking, male, Eastern Cooperative Oncology Group performance status (ECOG PS) = 0/1, age < 65/≥65 while SICI+CT for low tumor mutation burden (TMB), non-smoking, and female subgroups, and DICI for high TMB subgroups. Conclusions In the first-line therapy for advanced wild-type NSCLC, both SICI- and DICI-based treatments could bring significant overall advantages over chemotherapy, with comparable outcomes of efficacy and ≥3AEs. DICI-based treatments were more effective than SICI-based treatments in squamous and PD-L1 <1% subgroups. For most populations, DICI+chemotherapy could be the best choice with a survival benefit, while SICI+chemotherapy has established its position actually. Systematic Review Registration [PROSPERO], identifier [CRD42020184534].